Feminist entrepreneurship: A critique of the capitalist economic system - Sopian Tamrin; Muhammad Syukur; Firdaus W Suhaeb (Jurnal Anifa: Studi Gender dan Anak, 2025)
This study presents a literature review on feminist entrepreneurship as a critique of the capitalist economic system, which often fails to uphold gender justice and ecological sustainability. The study draws on academic journals, books, and reports that examine the socio-economic and environmental consequences of capitalism particularly in relation to gender. The data were analyzed thematically using a feminist critical theory framework, with a focus on ecofeminism. The findings suggest that feminist entrepreneurship offers an alternative model that prioritizes not only economic outcomes but also values of solidarity, inclusivity, and sustainability. It seeks to challenge and transform discriminatory economic structures by empowering women, redistributing resources, and promoting community-based business models. Feminist entrepreneurship also elevates the importance of care work and ecological stewardship—elements often marginalized in capitalist systems. This paper argues that feminist entrepreneurship can serve as a strategic response to gender inequality and contribute to the development of a more inclusive and human-centered economy. Ultimately, it reflects the author's engagement in discursive resistance to capitalism and calls for the creation of a more equitable economic paradigm.